Східнотрипільська і західнотрипільська культури: міф чи реальність? - Бурдо, Н.Б. (Археологія і давня історія України, 2021)
Проблематика культурогенезу первісності є
однією з центральних у наукових дослідженнях
В. В. Отрощенка. Зокрема він торкався культурогенезу та структури культурного комплексу Трипілля-Кукутень, дослідження яких набуло актуальності в останні десятиліття ХХ ст. Поява нових
джерел та методів спонукає дослідників до осмислення феномену Трипілля-Кукутень на новому рівні. Помітна тенденція виділення замість структурних підрозділів культурної спільності окремих
археологічних культур. На рубежі ХХ —ХХ І ст. у
вітчизняному трипіллєзнавстві набула поширення концепція, що передбачає бінарну схему розподілу трипільської культури на «східнотрипільську» та «західнотрипільську» культури. Втім, подібна
новація не виглядає достатньо обґрунтованою як
на рівні методичних засад, так і на рівні формального аналізу конкретних матеріалів. З’ясування
реальної структури культурного комплексу Трипілля-Кукутень показує її багатогранність і доводить штучність розподілу його трипільської частини на дві археологічні культури. Problems of culturogenesis and structure of the cultural
complex of Trypillia-Сucuteni become relevant
in the last decades of the XXth century. The emergence
of new sources and methods encourages researchers to
understand the phenomenon of Trypillia-Сucuteni on a
new level. There is a noticeable tendency to single out
individual archaeological cultures instead of structural
subdivisions of the cultural community at the turn of the
XX—XXIth centuries. The binary scheme of the division of
the Trypillia culture into the «East Trypillia» and «West
Trypillia» cultures became popular in the national Trypillia
studies. However, such an «innovation» is not sufficiently
substantiated both at the level of methodological
principles and analysis of specific materials. Elucidation
of the real structure of the cultural complex of Trypillia-
Сucuteni shows its versatility and proves the artificiality
of its division into two archaeological cultures, which is
proposed by O. V. Tsvek and S. M. Ryzhov.
The division of the Trypillia-Сucuteni cultural complex
into separate archeological cultures (two or more) is
impossible until its final stage CII, because almost all its
structural units are selected on the basis of ceramic traditions,
and the other parameters (character of house-building,
tools producing, sacred tradition) are more or less the
same. All structural units combine a genetic link with the
Precucuteni-Trypillya A times, which demonstrates all
the features of the Trypillia-Сucuteni cultural complex as
a whole, with the exception of ceramic traditions. These
traditions are the most dynamic, act as an indicator of the
cultural identity of certain groups of the population and
reflect the structure of the cultural complex.
The structure of the cultural complex Trypillia-
Сucuteni is a spatio-temporal continuum, its complexity
is due to dynamic and multifaceted processes
of internal transformations of individual units of the
structure, the interaction of traditions and innovations,
constant contacts between them, the movement of specific
groups, their interaction with surrounding cultural
complexes. The binary concept of the «East Trypillia»
and the «West Trypillia» cultures, which became too
popular today, is an artificial construction and does not
reflect the real structure of Trypillia Culture.